THE GENUS MINISTRYMON CLENCH 1961 IN CHILE AND A NEW SPECIES FROM THE NORTHERN DESERT BIOTIC PROVINCE (LEPIDOPTERA: LYCAENIDAE) (Acta Entomológica Chilena, 2022)
Based on a survey of type specimens, species of the New World hairstreak butterfly genus MinistrymonClench are listed and first records from Chile reponed. M. azia Hewitson reaches its southwesternrange extreme in xeric Coastal habitats near the Chile/Perú border (Arica). M. quebradivaga, newspecies, is described from quebrada habitat in the Northern Desert Biotic Province (Quebrada Vitor,Pampa Tamarugal), Tarapacá Región. This new species shares characters with two subgroups ofMinistrymon and is probably a primitive relict. At least two other Lepidoptera studied to date show thepattern of distribution and endemism exhibited by Ministrymon in Chile.
Keywords: Ministrymon quebradivaga n. sp.; M. azia\ Chile I. Región Tarapacá; Lycaenidae; Distribution